Rehabilitation Efforts for Drugs Addictives Through Islamic Education Approach at Islamic Tarbiyah Islamic Boarding School Lhokseumawe City - Miswar, Anna (Wasatha: Jurnal Studi Islam dan Humaniora, 2023)
When they are down, because they are far from religious values, they look for antidepressants for depression, one of which is drugs. The problem of drug abuse needs to be taken seriously and become a shared responsibility. This study aims to: (1) describe the efforts to rehabilitate drug addicts through the PAI approach at the Islamic Boarding School of Tarbiyah Mee Kandang, Muara Dua District, Lhokseumawe City, (2) describe the form of the PAI approach in the rehabilitation of drug addicts at the Islamic Tarbiyah Islamic Boarding School, Meunasah Mee Kandang Village, District Muara Dua, Lhokseumawe City, (3) described the obstacles to efforts to rehabilitate drug addicts through the PAI approach at Islamic Tarbiyah Islamic Boarding Schools in Meunasah Mee Kandang Village, Muara Dua District, Lhokseumawe City. This research is a field study using a qualitative approach, carried out at the Tarbiyah Islamiyah Islamic Boarding School, Meunasah Mee Kandang Village, Muara Dua District, Lhokseumawe City. Data collection techniques through interviews, observation and documentation. Data analysis techniques were carried out through data reduction, data presentation and data verification. The results of the study show that: 1) efforts to rehabilitate drug addicts through PAI at Islamic Tarbiyah Islamic Boarding Schools: (a) faith education (b) religious education, (c) moral education, (e) social education so that drug addicts have skills, 2) forms of approach PAI in the rehabilitation of drug addicts at the Tarbiyah Islamiyah Islamic Boarding School: a psychological approach and a socio-cultural approach, 3) obstacles encountered in efforts to rehabilitate drug addicts through the PAI approach at the Tarbiyah Islamiyah Islamic Boarding School: there is no financial assistance from the government, in addition to dealing with residents of different character , and also residents who are mentally ill.